Application and Challenges of BIM Technology in China's Integrated Utility Tunnels - Feng, Yang; Wai Yie, Leong (INTI International University, 2024)
In the context of rapid urbanization, integrated utility tunnels present an innovative solution by consolidating various pipelines into a unified underground system, improving construction efficiency and urban management. This paper explores the role of Building Information Modeling (BIM), a breakthrough technology that enhances project design, simulation, and construction efficiency through digital modeling. BIM technology is optimizing utility tunnel construction by enabling better planning, monitoring, and collaboration through 3D and 4D modeling. Using a PESTEL analysis framework, this study evaluates BIM's application in integrated utility tunnels in China and its potential for advancing the digital transformation of urban infrastructure. The research reveals how BIM can enhance the informatization and intelligence of utility tunnels and discusses the future opportunities and challenges for its expansion in China's urbanization efforts.